Knowledge management innovation readiness - Mahmod, Razmah; Wan Aris, Yon Bahiyah; Rosnan, Herwina (2011)
Knowledge Management (KM) program are profound among big organisations as it stimulates innovations. Innovation is crucial to ensure organisation's survival in this globalised world. Innovation is especially important for SMEs to remain competitive. Hence, the present study is to examine the readiness to innovate among SMEs in Malaysia. Specifically, the study investigates factors that could influence the readiness to innovate among SMEs. Data was collected through questionnaire survey among SMEs in Klang Valley. Data was then analysed using statistical package for social science (SPSS) software version 16.0. There are two statistical test conducted namely descriptive and inferential statistics. The result of descriptive statistics was presented in the form of frequency and percentage. For inferential statistics, Pearson correlation and multiple regression analysis were conducted. Reliability testing also was conducted to measure the goodness of the data and all of the cronbach's alpha score are more than 0.7 for each variable. The result of Pearson correlation showed that there are positive relationship between all the independent variables and readiness to innovate. However, multiple regression analysis showed that only four out of nine independent variables are significantly related to readiness to innovate. The findings indicate the most influential factor found to significantly influence the SME sector's in Malaysia readiness to innovate consists of organizational policy, a knowledge friendly culture, an information system culture and training.